ANALISIS SEMIOTIKA PADA CITRA BRAND MELALUI LOGO OLEH PERUSAHAAN RABBANI - Mia Tania (CV. Lafadz Jaya, 2026)
Logo serves as a company's means of expression—utilizing shapes, colors, typography, symbols, and specific text—to shape the image, identity, and public perception, thereby differentiating one brand from another. A specific method is required to delve deeper into the meanings, signs, and understandings embedded within a logo. This study focuses on interpreting the symbols found in the Rabbani logo through the lens of Charles Sanders Peirce’s semiotic analysis, which categorizes signs into three types: icons, indices, and symbols. The findings reveal that the Rabbani logo is unique in its implementation, featuring the Arabic letter “Ro” in three sizes (large, medium, and small), the use of the color pink, and a box-like shape with a rounded top-right corner. The Rabbani logo functions not merely as an identifier but as a visual entity that constructs meaning through various Islamic elements.